Intergration of Islamic input in medical curriculum - Universiti Sains Islam Malaysia (USIM) experience - Jamaludin, Jamilah; Azmi, Ahmad Najib; Mohd Rani, Dzulkhairi; Osman, Ariff; Nik Ismail, Nik Mohd Nasri (Kulliyyah of Medicine, International Islamic University Malaysia, 2014)
Muslim doctors are those qualified doctors who practise their professional knowledge and skills in line with Islam and upholds the highest standards of ethical and professional behaviour. The medical curriculum of the Faculty of Medicine and Health Sciences of Universiti Sains Islam Malaysia (USIM) was designed with the integration of Islamic input which aims at producing doctors who are able to practise medicine that is integrated with Islamic, moral and ethical values. Halaqah Studies and Fundamental Islamic Knowledge (FIK) courses such as History of Medicine in Islam, Science and Medicine in Quran and Sunnah, Akhlak and Tasawuf, Islamic Jurisprudence and Medical Ethics and Fiqh Issues are taught to students during the pre-clinical and clinical phases. Memorization of selected Quranic verses throughout the programme aim to get the students to apply the verses of the al-Quran into practice in everyday life and especially in their clinical practice. Islamic values are emphasised during doctor-patient interactions in all clinical postings. Islamic knowledge and values integrated in the curriculum are assessed in written and clinical examinations. The outcome of the integration of the Naqli component in the medical curriculum has been demonstrated positively by the students in the patient management problems and clinical consultations. Studies on the outcome of the integrated Islamic input in the medical curriculum among the clinical students and graduates are being carried out.